Hubungan Kekuasaan Kepala Desa dan Badan Permusyawaratan Desa dalam Penyelenggaraan Pembangunan di Desa Mundinggasa dan Desa Natanangge Kecamatan Maukaro Kabupaten Ende Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Jalo, Fransiska Godhi; Tupen, Rafael Rape; Ratu Udju, Hernimus (Artemis Law Journal, 2024)
The purpose of this study, conducted by the author, is to generally understand and analyze the relationship between the village chief and the village deliberative body (Badan Permusyawaratan Desa) in the implementation of development in Mundinggasa and Natanangge Villages. It aims to identify and examine the obstacles that hinder the relationship between the village chief and the village deliberative body in the implementation of village development in Mundinggasa and Natanangge Villages, using an empirical juridical method and analyzing qualitative descriptive data. The research focus includes the relationship between the village chief and the village deliberative body, development planning, implementation, supervision, and the impact of the relationship on the administration of the village. Data were directly obtained from the research location involving 12 respondents. The results of the study conducted by the author show that the relationship between the village chief and the village deliberative body in development planning is generally good. However, the main issue lies in the lack of communication and coordination between the village chief and the village deliberative body, resulting in the implementation of village development not proceeding smoothly and being vulnerable to exceeding the specified time frame in the development plan. A positive relationship can bring about beneficial changes in village governance, but a lack of harmony in the relationship, due to insufficient transparency from the government institutions, can lead to negative impacts.